2021
DOI: 10.1111/nph.17130
|View full text |Cite
|
Sign up to set email alerts
|

Histone H3 lysine4 trimethylation‐regulated GRF11 expression is essential for the iron‐deficiency response in Arabidopsis thaliana

Abstract: Summary Iron (Fe) homeostasis in plants is controlled by both transcription factors (TFs) and chromatin remodeling through histone modification. To date, few studies have reported the existence of histone modification in maintaining the Fe‐deficiency response. However, the reports that do exist shed light on various histone modifications, but knowledge of the activation mark in Fe‐deficiency response is lacking. By using a forward genetics approach, we identified a crucial allele for Fe‐deficiency response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…PRC2-mediated H3K27me3 (histone 3 lysine 27 trimethylation) modulated the expression of FIT-dependent genes under iron deficiency (Park et al, 2019). Recently, NRF2/ELF8 controls the expression of the root-specific gene GRF11 through H3K4me3 and maintains the Fe-uptake machinery (Singh et al, 2021). Taking into account that the Cnr epimutant displayed increased sensitivity to Fe-deficiency response (Figure 1), it is interesting to envision whether epigenetic modifications, especially DNA methylation, play potential roles in Fe-deficiency responses.…”
Section: Discussionmentioning
confidence: 99%
“…PRC2-mediated H3K27me3 (histone 3 lysine 27 trimethylation) modulated the expression of FIT-dependent genes under iron deficiency (Park et al, 2019). Recently, NRF2/ELF8 controls the expression of the root-specific gene GRF11 through H3K4me3 and maintains the Fe-uptake machinery (Singh et al, 2021). Taking into account that the Cnr epimutant displayed increased sensitivity to Fe-deficiency response (Figure 1), it is interesting to envision whether epigenetic modifications, especially DNA methylation, play potential roles in Fe-deficiency responses.…”
Section: Discussionmentioning
confidence: 99%
“…H3K4me3, the trimethylation of histone 3 lysine 4, generally leads to gene activation (Liu et al, 2010;Xiao et al, 2016). Using a forward genetics screen in Arabidopsis, Singh et al (2021) identified a regulator of iron deficiency response, NON-RESPONSE TO Fe-DEFICIENCY2 (NRF2). In Arabidopsis, NRF2 is known as EARLY FLOWERING8 (ELF8), which regulates FLOWERING LOCUS C (FLC) expression via H3K4me3 (He, 2009).…”
Section: H3k4me3mentioning
confidence: 99%
“…Under iron deficiency, AtNRF2/ELF8 is required for AtGRF11 expression as it modulates H3K4me3 levels at its transcription start site (Singh et al, 2021). While AtGRF11 does not directly interact with AtFIT, it acts downstream of NO to induce AtFIT expression in iron deficient roots (Singh et al, 2021). In the nrf2 mutant, AtGRF11-regulated iron uptake was repressed and iron transport and storage genes were downregulated.…”
Section: H3k4me3mentioning
confidence: 99%
“…Chen et al 2010; Shen et al 2014; J. Li et al 2017; An et al 2020; Gómez-Zambrano et al 2018), and height or size of the plant (CLAVATA, GH9C2, ELF8, NSL1, TUA6) (Glass et al 2015; Markakis et al 2012; Noutoshi et al 2006; Fukunaga et al 2017; Singh et al 2021; Fal et al 2017; He 2004; Hoson et al 2014; Xiong et al 2013; Whitewoods et al 2020).…”
Section: Resultsmentioning
confidence: 99%